2013
DOI: 10.15666/aeer/1104_593610
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Normal and Black Light Type Trapping Results Upon the Wingspan of Moth Species

Abstract: Abstract. In the last decade several researchers found relation between the wingspan size of moths and their light sensitivity. Generally, moths with larger wingspan have higher light sensitivity. We tested these findings using the catch data of 378 Macrolepidoptera species from 19 black light (BL, 125 W) and normal light trap (100 W) pairs of the Hungarian Light Trap Network. We have found that wingspan size of about 25 mm is the limit below which some species were trapped more effectively by normal light tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…5c, d). These findings are consistent with the results of studies that showed that moths with relatively large eyes and a relatively large body mass were attracted to light dominated by shorter wavelengths [48,63,67], although the degree of attraction varied between moth taxa [46]. One might speculate that their distinct preferences are due to the distinct spectral sensitivities of the compound eye.…”
Section: Discussionsupporting
confidence: 90%
“…5c, d). These findings are consistent with the results of studies that showed that moths with relatively large eyes and a relatively large body mass were attracted to light dominated by shorter wavelengths [48,63,67], although the degree of attraction varied between moth taxa [46]. One might speculate that their distinct preferences are due to the distinct spectral sensitivities of the compound eye.…”
Section: Discussionsupporting
confidence: 90%
“…Generally, moths with larger wingspans have a greater sensitivity to light . One study analyzed the wingspans of 378 species of moth caught by light traps equipped with different light sources, and the results suggested that the number of moths caught by light traps depended on the type of light source and the wingspan of the moths . A light trap equipped with a suitable light source can be somewhat adapted for the target insect species.…”
Section: Considerable Problems In the Application Of Light Trapsmentioning
confidence: 99%
“…et Schiff. (Járfás 1977;Nowinszky 2013). Laboratory measurements showed two number of species and higher abundance (van Langevelde et al 2011;Barghini and Medeiros 2012;Kadlec et al 2016;Brehm 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are quite a lot of data on the effects of weather (temperature, wind strength, humidity, air pressure, etc. ), moon phases and other environmental factors on the efficiency of light traps (Kiss 2002;Nowinszky 2003;Nowinszky et al 2014), while spectral distribution is one of the most important parameters affecting the attractivity and selectivity of light sources (Nowinszky 2003). Light sources emitting relatively large amount of UV light generally perform better in catching of night-active insects than others (Blomberg et al 1976;Ashfaq et al 2005;Cowan and Gries 2009), since beyond the visibility and the spectral distribution of the lamp, at least a minimal amounts of UV radiation are a crucial factor of the attractiveness (Barghini 2008, Barghini andMedeiros 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation